(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The article describes the characteristics of the development of foreign trade and its factors on an analytical basis. In particular, Uzbekistan’s trade relations with Central Asian countries and its development trend are analyzed. Considerations were also made regarding the prospects of Uzbekistan’s trade with the countries of Central Asia and its directions